A multi-group structural equation modelling investigation of the measurement invariance of the Campbell Interest and Skill Survey (CISS) across gender groups in South Africa - Donnelly, Clayton (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2009.